The design and application of a customized navigation board for lumbar disc ablation. (31st October 2017) - Zhang, Yan; Gu, Diebao; Ji, Dafeng
Abstract: Purpose: This paper aimed to explore the design and application of a customized navigation board for lumbar disc ablation. Methods: Eight cases of lumbar disc herniation (diagnosed by spiral computerized tomography, CT) to be treated via intervertebral ablation using a path from the skin to the herniated intervertebral disc were included. The lumbar vertebrae, sacrum, and skin (adhered to a standard base, Figure 1) were reconstructed based on continuous spiral CT slices. The path was designed by the surgeon (Figure 2) to be line between the base and the puncture point, and was guided by the navigation board. The board was prototyped and used in ablation localization as a guide canal. The intra- and post-operative complications were recorded during the operation and 48-hours post operation, respectively. Results: In all eight cases, target discs were punctured after a duration ranging from 6 to 13 minutes. No complications were observed either during the operation or at 48 hours post-operatively. Conclusion: This customized navigation board could promote the accuracy and diminish the duration of intervertebral disc ablation. A stereolithography apparatus (SLA) and photosensitive resin could generate a customized reverse guide board with high fidelity for intervertebral disc ablation. Manually performed rigid registration can meet the accuracy requirements. The results presented in the present paper demonstrated that rapid prototyping via an SLA and photosensitive resin could maintain the accuracy and dynamic stability of a customized navigation board for lumbar disc ablation.